THE PROBLEM OF SOVEREIGNTY IN THE PHILOSOPHY OF THE 17th–18th CENTURIES (T. HOBBES AND S. PUFENDORF) - Našit Ferati (Pravo, 2025)
This study presents a philosophical reflection on the question of sovereignty, viewed through a comparative analysis of two philosophers: Thomas Hobbes and Samuel Pufendorf. The field of inquiry lies between political philosophy and the philosophy of law. The literature review centers on prominent thinkers such as Machiavelli, Bodin, Spinoza, Locke, Montesquieu, Rousseau, Kant, and others, in order to provide a broader and deeper understanding of the questions surrounding sovereignty. The bibliographic research is oriented toward a comparative and analytical approach. A foundational understanding of Hobbes’s and Pufendorf’s philosophical positions is essential, as the comparative analysis aims to articulate their discourse on topics such as the idea of objective social unity and the ways in which national sovereignty is concretized. The comparison focuses on the form and substance of the social contract. At the core of the discussion is the relationship between popular (political) sovereignty and state sovereignty. The discourse highlights the nature of sovereign power and the issue of freedom, challenging the principle of representativeness. Positioned between the idea of indivisible force and the power to realize justice, sovereignty is situated within the conflicting contexts revealed through this comparison. The study further explores the political-legal system and the concept of the rule of law. Additionally, it addresses the complex relationship between internal and external sovereignty, wherein the essence of sovereignty is often compromised.